2023
DOI: 10.1002/ajhb.23871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dietary inflammatory potential on the trajectory of body adiposity in a Brazilian cohort of university students

Abstract: Objectives University students are vulnerable to unhealthy eating habits that characterize a proinflammatory diet. This study aimed to estimate the dietary inflammatory index (DII) and its association with the trajectory of body adiposity markers in university students. Methods The study analyzed data from 685 students entering a Brazilian public university in 2016 and 2017 and followed until 2018. DII was estimated from 39 dietary parameters obtained by 24‐h dietary recall. Body adiposity was assessed by anth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…This association in literature was prominent especially for abdominal obesity indicators such as WC and WHR (de Souza et al, 2023;Ariya et al, 2020; , 2016). In a cohort of Brazilian university students, after adjustments at baseline, the DII score showed a positive association with increased WC among women (de Souza et al, 2023). Similarly, in a study conducted with Spanish adults, it was shown that individuals in the highest proinflammatory category (last quintile), also had the highest WC values.…”
Section: Nfs 544mentioning
confidence: 69%
See 4 more Smart Citations
“…This association in literature was prominent especially for abdominal obesity indicators such as WC and WHR (de Souza et al, 2023;Ariya et al, 2020; , 2016). In a cohort of Brazilian university students, after adjustments at baseline, the DII score showed a positive association with increased WC among women (de Souza et al, 2023). Similarly, in a study conducted with Spanish adults, it was shown that individuals in the highest proinflammatory category (last quintile), also had the highest WC values.…”
Section: Nfs 544mentioning
confidence: 69%
“…Similarly, in a study conducted with Spanish adults, it was shown that individuals in the highest proinflammatory category (last quintile), also had the highest WC values. The association aforementioned in both men and women was the strongest compared to the associations between other anthropometric traits and the most proinflammatory diet (de Souza et al. , 2023).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations